Hubungan Ukuran-Ukuran Usus Halus Dengan Berat Badan Broiler - Sulaiman Ibrahim (Jurnal Agripet, 2008)
Association of small intestine measurements with body weight in broilersABSTRACT. The main objective of the present study was to investigate the association of small intestine measurements with body weight in broilers. Sixty five weeks old unsex broiler chicks (CP 707) were used. All birds were leg-banded and alloted to 60 cage units and than were fasted for 10 hours but water given. All birds were weighed individually and then sacrificed by neck vein bleeding. Small intestine was dissected individually to determine length and wide. All data were subjected to statistical analysis: correlation and simple linear regression, analysis of variance and t-test. The length of small intestine, duodenum, and jejunum/ileum were each strongly correlated with body weight: r = 0,88; P 0,01; r = 0,71; P 0,01; and r = 0,80, P 0,01 respectively. The wide of duodenum and jejunum/ileum were each closely correlated with body weight: r = 0,90; P 0,01; and r = 0,86; P 0,01 respectively. Results of study indicated that there were strong association between small intestine measurements and body weight in broilers.